Developing a Frame Design for Airport Pavements Maintenance Management System - Nooruldeen Mohammed Kareem; Asma Thamir Ibraheem (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Software that depends on available information provides answers, solutions, or diagnoses by following techniques that aim to imitate the mental processes and apply the knowledge of an expert in any particular subject. Using an expert system has a number of advantages over typical computerized models. Expert systems are successful at issue solving because they include a large number of experts. Human knowledge and thought are just too complicated to capture and use in an analytical technique. For the past 20 years, that expert system has been used in paving applications, mostly for highway networks. The number of expert systems created for airport pavement is still minimal. This Paper describes the initial development and methodological method of developing and validating the motion test method using video and photography, which increases the degree of automatic detection of road stress; to develop a descriptive strategy for airport road maintenance strategies, adapted to the Baghdad international airport system, using modeling strategies to predict road performance and service definition and implementation standards; and to develop a software, then evaluated it by applying to an existing computer programs that can be used as a decision support tool.